Blake Harrsch. «Unveiling of the Sun» - Harrsch, Blake (Young Scholars Grinchenko – Seton International Journal, 2021)
Abstract. This poem, inspired by Ta-Nehisi Coates’ Between the World and Me, engages the major lessons of his book detailing his lived experiences as a Black man in America. The author captures Coates’ claim that Black people cannot shy away from the harsh realities of racism embedded in American society, while White people have the privilege of ignoring such truths as they are not the target of its harmful implications. Ways in which Coates critiques the discussion and beliefs surrounding race in America, both past and present, are explored.